2023
DOI: 10.33884/jif.v11i01.6593
|View full text |Cite
|
Sign up to set email alerts
|

Peran Ethical Hacking Dalam Memerangi Cyberthreats

Qorry Aina Fitroh,
Bambang Sugiantoro

Abstract: Upaya digitalisasi dan optimalisasi berbagai hal dalam dunia modern tentunya akan menyoroti berbagai isu yang berkaitan dengan cybersecurity seperti pelanggaran data, pelanggaran keamanan, dan sebagainya. Ethical hacking dan kebutuhannya di masa mendatang tidak dapat dihindari. Teknologi ethical hacking menyebar hampir dalam setiap aspek kehidupan, terutama industri komputer yang membutuhkan perlindungan terhadap data penting dan harus ditangani dengan teknologi yang tepat. Ethical hacking bertujuan menemukan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Although it is a well-organized, systematic, and generic framework, its idea and structure have never been applied to other sectors. Although there are some examples of the use of COBIT in agriculture [49,50], they refer exclusively to the governance and management of IT. The only identified exception was in healthcare where the results of a preliminary study suggested the adoption of COBIT framework elements to represent typical healthcare processes [18].…”
Section: Cobit As the Basis For The Standard Process Model For Health...mentioning
confidence: 99%
“…Although it is a well-organized, systematic, and generic framework, its idea and structure have never been applied to other sectors. Although there are some examples of the use of COBIT in agriculture [49,50], they refer exclusively to the governance and management of IT. The only identified exception was in healthcare where the results of a preliminary study suggested the adoption of COBIT framework elements to represent typical healthcare processes [18].…”
Section: Cobit As the Basis For The Standard Process Model For Health...mentioning
confidence: 99%